Effects of Opportunities to Learn on Peruvian Students’ Science Achievement in Program for International Student Assessment 2015 - Bazán-Ramírez, Aldo; Hernández-Padilla, Eduardo; Bazán-Ramírez, Wilfredo; Tresierra-Ayala, Miguel (Frontiers in Education, 2022)
Opportunities to learn (OTL) are considered important variables to enable equitable educational standards in teaching. The main objective of this work was to test a five-level hierarchical model to explain the general achievement and science competencies of Peruvian students in the Program for International Student Assessment (PISA) 2015, controlling for the student’s age and gender, and the economic, social, and cultural status, both for the student (ESCS) and the school (MESCS). The Peru database was taken from PISA 2015 and was based on the results of 6,971 Peruvian students from 281 schools. The 10 plausible values of performance in science reported by PISA 2015 were used, and each of the four sub-competencies was evaluated. The values weighted likelihood estimate (WLE) of the following composite variables were standardized: (1) In teaching-learning activities, the disciplinary environment in science classes, teaching support in science classes at the students’ choice, and inquiry-based science teaching-learning practices; teacher-directed science instruction were considered. (2) For the formative evaluation factor, feedback, student perception about the evaluation, and adaptation of the instruction to the formative evaluation were considered. (3) The control variables were as follows: the age and gender of the students, the index of social, economic, and cultural status (ESCS) at the student level, and the average of the index of the social, economic, and cultural status of each school (MESCS), as well as the interaction of OTL variables with ESCS. The results of the linear hierarchical analysis showed that the achievement of Peruvian students in science in PISA 2015 (general competence) is mainly due to feedback perceived, adaptive instruction, teacher-directed science instruction, and inquiry-based science teaching-learning practices. The feedback perceived and the inquiry-based science teaching predicted negatively and significantly to science performances. The effect of inquiry-based science teaching-learning on science achievement decreased as hierarchical analysis models became more complex and decreased substantially when simultaneously interacting with perceived feedback, the student gender, and ESCS. The results also showed that the gender, the ESCS of the students, and the MESCS of the school were significant and positive predictors of academic performance. When considering each of the scientific competencies evaluated, the models are like the general score. Mainly, the MESCS of the school controls or diminishes the effect that the instructional variables have on science performance, except for the negative effect of feedback on academic performance, even when the ESCS is controlled by the school level.